Early Exposure to Antibiotic Therapy after Common Infections as a Risk Factor for the Development of Respiratory Atopy - Alketa H. Bakiri; Ervin Ç. Mingomataj (Disease and Health Research - New Insights Vol. 1, 2024)
Antibiotics are one of the most frequently prescribed medications and their rational use has become an essential topic in clinical care. In this context, we have witnessed a dramatic increase in the prevalence of respiratory allergies during the last decades. The infections’ role in the prevalence of respiratory allergic diseases is attributed to the antagonism between: a) induction of T helper (Th) 1 immune response by human organisms; and b) manipulation of the human immune response toward Th2 profile by common infective agents to increase their surviving opportunity. This work proposes that extensive antibiotic exposure during neonatal and early childhood plays an important role in the increasing epidemiological trend. It is believed that antibiotic exposure during early childhood has also provided better survival opportunities for atopic individuals with an inadequate immune defense against common infections, deviating, therefore, from the genetic background of the general population toward the Th2 profile. Considering this, we suggest that Th2 profile frequency (and consequently atopic phenotype prevalence) can be increased along an individual lifespan after extensive antibiotics introduction until the entire population is exposed to them during childhood. This hypothesis may explain findings on epidemiological surveys, which report a prevalence increase among adults in industrialized countries between the 1970s and 2000s; in recently-developed countries, this trend began only at the end of the 1980s. These arguments support the conclusion that infections will manipulate human immunity over generations. In contrast, actual antibiotics can increase the prevalence of respiratory allergies among a population only along with individual longevity. These findings may help develop future management strategies to treat respiratory allergic or infective pathologies. The knowledge of the mentioned interactions may help us develop better etiological theories about respiratory allergic diseases that can replace the actual theory or incorporate it as an additional possible scenario.